2022
DOI: 10.18203/2349-3291.ijcp20221068
|View full text |Cite
|
Sign up to set email alerts
|

A study of clinical profile and outcome of COVID-19 in children

Abstract: Background: COVID-19 has become a major public health crisis around the world. This study aimed at identifying the different clinical presentations of children who were tested positive for SARS-COV-2.Methods: Descriptive and prospective study of the children who were seen over the fever clinic and were admitted to the Sapthagiri institute of medical science and research centre over a period of 4 months from November 2021 to February 2022.Results: Among the 251 children admitted to the hospital majority of them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…18 Similarly, Nagaraj MV et al also reported majority of children were male (52.5%). 19 Initially it was thought that the disease is acute respiratory illness and affects the respiratory system mainly but it affects other systems also. In our study, the most commonly involved systems were respiratory (42, 66.7%) followed by gastrointestinal (28, 44.5%) and neuromuscular (13, 20.6%).…”
Section: Corona Virus Disease 2019 (Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…18 Similarly, Nagaraj MV et al also reported majority of children were male (52.5%). 19 Initially it was thought that the disease is acute respiratory illness and affects the respiratory system mainly but it affects other systems also. In our study, the most commonly involved systems were respiratory (42, 66.7%) followed by gastrointestinal (28, 44.5%) and neuromuscular (13, 20.6%).…”
Section: Corona Virus Disease 2019 (Covid-19mentioning
confidence: 99%
“…14 In the recent literatures, the severe disease ranges from 7% to 65%. 19,23,24 Length of hospital stay (LOS) of covid-…”
Section: Corona Virus Disease 2019 (Covid-19mentioning
confidence: 99%
See 1 more Smart Citation